Range fires. - Trotta AM (Consumer Product Safety Review)
Early morning, January 3, 2001: A Delaware resident is heating cooking oil on a stove burner set on 'high. ' While waiting for the oil to get hot, the resident falls asleep. The oil ignites, and the fire spreads to the kitchen cabinets, countertop, and walls. The thick smoke spreads throughout the house, claiming the lives ofits 11 occupants, seven of them young children.